Design and Synthesis of Novel Aspirin-Caffeic Acid Ester Hybrids for Cardioprotection with Reduced Risk of Hemorrhagic Stroke - Shi, Zhi-Hao; Li, Nian-Guang; Tang, Yu-Ping; Shi, Qian-Ping; Zhang, Wei; Zhang, Peng-Xuan; Dong, Ze-Xi; Li, Wei; Duan, Jin-Ao (Asian Journal of Chemistry, 2015)
A series of novel aspirin-caffeic acid ester hybrids for cardioprotection with reduced risk of hemorrhagic stroke were designed and synthesized by coupling aspirin and caffeic acid esters inspired by NCX-4016. The synthesized compounds were evaluated for their in vitro antiplatelet aggregations induced by ADP and antioxidant activity of the caffeic acid esters which could be released from the hybrids by esterases in vivo like NCX 4016 were determined by DPPH assay. The results showed that compound 3d exhibited potent antiplatelet activity than aspirin and its intermediate caffeic acid isopropyl ester (2d) showed good antioxidant activity and thus could be considered to be novel potent cardioprotectic drug candidates with reduced risk of hemorrhagic stroke.